2002
DOI: 10.1002/jso.10163
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of heparanase messenger RNA expression in hepatocellular carcinoma

Abstract: Enhanced heparanase mRNA expression may not be a good biological marker in HCC. J. Surg. Oncol. 2002;81:148-154.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…Patients in the study of ElAssal et al [14] were mainly infected with HCV, but most HCCs in China were related to HBV infection and posthepatitic cirrhosis, few were infected with HCV. In addition, our conclusions are different from those of Ikeguchi et al [15] , in which relative heparanase mRNA expression level in HCC was significantly lower than that in noncancerous liver tissues, and tumor heparanase expression did not correlate with tumor differentiation, tumor stage, or patient prognosis. Both the discrepancy of hepatitis virus and experimental methods could contribute to the different results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Patients in the study of ElAssal et al [14] were mainly infected with HCV, but most HCCs in China were related to HBV infection and posthepatitic cirrhosis, few were infected with HCV. In addition, our conclusions are different from those of Ikeguchi et al [15] , in which relative heparanase mRNA expression level in HCC was significantly lower than that in noncancerous liver tissues, and tumor heparanase expression did not correlate with tumor differentiation, tumor stage, or patient prognosis. Both the discrepancy of hepatitis virus and experimental methods could contribute to the different results.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in their studies, over half of HCC patients (52.7%, 29/55) were accompanied with HCV infection, and few were associated with hepatitis B virus (HBV). Ikeguchi et al [15] found that relative heparanase mRNA expression level in HCC was significantly lower than that in noncancerous liver tissues (P<0.001), and that tumor heparanase expression did not correlate to tumor differentiation, tumor stage, or patient prognosis. They concluded that enhanced heparanase mRNA expression might not be a good biological marker for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Tissues-Many previous studies showed that elevated survivin expression was observed in human cancers of various origins (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Our data indicate that the intermediates in the cholesterol synthesis pathway, particularly FPP and GGPP, regulate survivin expression.…”
Section: Survivin Mrna Expression Correlates With Hmg-coa Reductase Mmentioning
confidence: 53%
“…Elevated survivin expression was observed in human cancers of various origins such as the breast (13), esophagus (14), stomach (15,16), colon (17,18), pancreas (19), liver (20), uterus (21), and ovaries (22) as well as in leukemias (23). Since survivin overexpression desensitized cancer cells to several anticancer agents (24) and to irradiation (25), which induce apoptosis, it acts as a resistance factor against these cancer treatment modalities.…”
mentioning
confidence: 99%
“…The majority of papers report on the elevation of HPSE mRNA and/or protein in HCC relative to both adjacent non-tumorous and normal liver tissue, and most investigations have found significant positive correlation between tumoral HPSE levels, HCC progression, and adverse prognosis. In some studies, however, the levels of HPSE mRNA were found to be decreased in HCC when compared to adjacent noncancerous tissue (Ikeguchi et al, 2002(Ikeguchi et al, , 2003, and mean HPSE mRNA expression was shown to be elevated in HCC relative to the healthy liver but lower than in fibrogenic diseases (TĂĄtrai et al, 2010). In explanation of a supposed tumor-inhibitory effect it has been proposed that, as opposed to the stimulatory effect of moderate HPSE activity, excessive HS fragmentation by HPSE may be detrimental to FGF-2 signaling and may therefore lead to increased apoptosis rates (Ikeguchi et al, 2003;Dong & Wu, 2010).…”
Section: Enzymes Involved In Hs Synthesis and Modificationmentioning
confidence: 99%